Suhela N. Singh, Ranjan, Kirti & Chandra, gen. n., a new genus for Conogethes alboflavalis Moore, 1888 (Lepidoptera: Crambidae, Spilomelinae) - N. Singh; R. Ranjan; J. S. Kirti; K. Chandra (SHILAP, 2022)
We describe a new genus for the Spilomelinae: Conogethes alboflavalis Moore, 1888, known to occur in India and Nepal. We provide diagnostic characters for the new genus and comparison with the closely related genera, Conogethes Meyrick, 1884 and Pycnarmon Lederer, 1863.